Alterations in male reproductive hormones in relation to environmental DDT exposure. (April 2018) - Bornman, Maria; Delport, Rhena; Farías, Paulina; Aneck-Hahn, Natalie; Patrick, Sean; Millar, Robert P.; de Jager, Christiaan
Abstract: DDT [1, 1, 1-trichloro-2, 2-bis ( p -chlorophenyl)-ethane] compounds are used for indoor residual spraying (IRS) to control malaria mosquitoes. DDT is an endocrine disruptor chemical in experimental conditions, but little is known of adverse effects related to living conditions with continual uptake across a time span by all possible means of exposure. Based on estrogenic and/or anti-androgenic effects found in animal studies, we hypothesized that chronic DDT/DDE exposures in men may be associated with changes in male reproductive hormones. We tested this hypothesis by compared the magnitude and direction of associations between DDT and DDE (1, 1-dichloro-2, 2-bis( p -chlorophenyl) ethylene) concentrations and male reproductive hormones in samples collected from IRS and non-IRS areas. We sampled a cross-section of 535 men (aged 18–40 years). Men living in IRS villages had significantly higher DDT and DDE concentrations compared with men from non-IRS villages. Men with DDT or DDE uptake (as reflected in detectable plasma concentrations) had significantly higher total-, free and bio-available testosterone (T), and lower follicle stimulating hormone (FSH) concentrations; lower luteinizing hormone (LH) concentrations were only evident with DDT uptake. To establish a dose-dependent effect, four sub-categories were defined. Men with the highest DDT (74–519 μg/g) and DDE (173–997 μg/g) concentrations had significantly higher total-, free and bio-available T, and lower FSH concentrations compared with subjects with non-detectable isomer concentrations. Estradiol concentrations were significantly higher in men with DDT and DDE concentrations in both the third (DDE: 27–172 μg/g; DDT: 5–73 μg/g) and fourth (DDE: 173–997 μg/g; DDT: 74–519 μg/g) categories. Men from IRS villages were significantly more likely to have higher total and bioavailable T as well as higher estradiol concentrations OR = 2.5 (95% CI 1.2, 3.2); OR 2.5 (95% CI 1.6, 4.0) and OR = 2.3 (95% CI 1.3, 4.1) compared to men from non-IRS villages, after controlling for age, BMI, personal use of pesticides, and smoking. Men living in IRS villages with life-long exposure (17.6 (±6) years) at the current residence with multiple exposure modalities incurred the highest degree of physiological imbalance over and above circulating isomer concentrations. Further studies are needed to elucidate the health implications of these findings. Highlights: Chronic DDT exposure may contribute to altered male reproductive hormone homeostasis. Men living in IRS villages incurred highest degree of hormonal imbalance. Men with high DDE, DDT concentrations had high T, E2, but low FSH, LH concentrations.